PENGARUH MEDIA SOSIAL DAN POTONGAN HARGA (DISKON) TERHADAP MINAT BELI PRODUK ROUGHNECK DI SHOPEE - Ivander Lioneld Sutanto; Lia Nirawati (Jurnal Pendidikan Ekonomi (JURKAMI), 2023)
In today's digital era, the role of e-commerce and Social Media is very important in developing and expanding a business, of course, providing Discounts is also a marketing strategy that can increase interest in buying products. This study aims to find out and analyze the influence of Social Media and Discounts on Interest in Buying Roughneck products on Shopee. This type of research is descriptive quantitative with an associative approach and uses multiple linear regression analysis. The sample in this study is consumers who attend Roughneck official stores at Shopee, totaling 2.1 million and are determined using the Slovin formula calculation with a sample of 100 respondents. The sampling technique used in this study was nonprobability sampling with a purposive sampling approach.  The results of this study show that simultaneously, the variables of Social Media and Discounts have a positive and significant effect on Buying Interest. Partially, the variables Social Media and Discounts have a positive and significant effect on the variables of Buying Interest